"The Soldier, the State, and the People—Costs and Benefits of Military Regimes": Evaluating the Essay "Guns and Butter: Child Mortality and the Mediators of Militarization". Issue 3 (July 2019) - Cyr, Arthur I.
The article "Guns and Butter: Child Mortality and the Mediators of Militarization" addresses the important subject of the social and political roles of militaries in nations above a minimum population size. Each national population is evaluated in terms of 10 characteristics including survival rates of children, level of armed conflict, economic development, political representation, and others. The authors draw a sharp distinction between social militarization and praetorian militarization. The essay is valuable in providing one dimension of the impacts of militaries on nations. However, qualitative information and analysis would greatly benefit this work. In this regard, the work of Samuel P. Huntington is instructive.